2019
DOI: 10.1002/cdq.12190
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Moments in Career Construction Counseling: Proposal for an Integrative Model

Abstract: This article advances understanding of career construction counseling (CCC) by viewing it through the lens of the innovative moments model (IMM) of how clients construct change. The IMM conceives clients’ narrative transformations as resulting from counselors prompting and clients reflecting on exceptions to a problematic self‐narrative (i.e., innovative moments; IMs) that emerges in counseling dialogues. On the basis of intensive IMM analysis of CCC case studies, the authors propose an integration of the 2 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 35 publications
0
29
0
1
Order By: Relevance
“…LDC emphasizes that individuals reflect on themselves and construct meaning based on continuous narration by considering the overall impact of the surrounding system, so as to generate expectations and motivation for the future (Cardoso et al, 2016a;Venter and Maree, 2020). Specifically, LDC focuses on people's interaction between themselves and the environment, establishes life trajectory through narration, and considers educational investment, work and life roles and meaning in life, so as to deal with the uncertainty of the future (Nota et al, 2016;Cardoso et al, 2019). In short, life-long, holistic, contextual and preventive are important characteristics of LDC (Savickas et al, 2009;Venter and Maree, 2020).…”
Section: What Is Life Design Counseling?mentioning
confidence: 99%
See 1 more Smart Citation
“…LDC emphasizes that individuals reflect on themselves and construct meaning based on continuous narration by considering the overall impact of the surrounding system, so as to generate expectations and motivation for the future (Cardoso et al, 2016a;Venter and Maree, 2020). Specifically, LDC focuses on people's interaction between themselves and the environment, establishes life trajectory through narration, and considers educational investment, work and life roles and meaning in life, so as to deal with the uncertainty of the future (Nota et al, 2016;Cardoso et al, 2019). In short, life-long, holistic, contextual and preventive are important characteristics of LDC (Savickas et al, 2009;Venter and Maree, 2020).…”
Section: What Is Life Design Counseling?mentioning
confidence: 99%
“…LDC aims to help clients reshape their lives through narration based on personal needs, interests, abilities and experiences (Maree, 2020b). Clients can rewrite their narrative identity, clarify their self-concept, establish life goals and explore possible life tracks (Savickas et al, 2009;Cardoso et al, 2019;Maree, 2020a).…”
Section: What Is Life Design Counseling?mentioning
confidence: 99%
“…It is a 'grand', inclusive theory on vocational and/or career choice and behaviour. Cardoso et al (2019) state that '[t]he fundamental goal of CCC is to enable clients to enact career change in the real world by first constructing new plans that elaborate their career themes and reconstruct a narrative identity with greater coherence and continuity' (p. 189). Career construction counselling (CCC) helps people narrate and draw on their own life stories (autobiographies) to construct their careers (Savickas, 2005;Savickas in Arthur, 2020).…”
Section: Career Construction Theorymentioning
confidence: 99%
“…Some researchers have found that if LDC counselors are not professional and especially lack active listening skills and empathy to clients, it would become difficult for counselors to be sensitive to comprehend problems of clients and take active roles in the development of reflexivity of clients (Guichard et al, 2012 ). Highly specialized LDC counselors could contribute to the client's innovative moments (IMs) and are more likely to use metaphors to identify the emotional needs of clients (Savickas, 2016 ; Savickas and Pouyaud, 2016 ), which play an important role in the change of clients (Cardoso et al, 2019 , 2020 ).…”
Section: Challenges In Life Design Counselingmentioning
confidence: 99%